(untitled) (Research, Society and Development, 2022)
Introduction: The worldwide prevalence of mental disorders points to the need for adequate and urgent holistic responses. The disconnection between science, health and politics before and during the pandemic of COVID-19 undermined the actions and reorganization of the reception and support system, especially for the most vulnerable, women and young people. Objective: To verify the prevalence of anxious, depressive and hopelessness symptoms in academics of a public university during the pandemic period. Methodology: This is an observational, cross-sectional study carried out with 128 undergraduate nursing students from a public university in the state of Paraíba, Brazil from January to March 2021. The recruitment was online and the data collection instrument was prepared on Google Forms with sociodemographic, health and coping strategies questions. Results: The study showed a majority of single female academics with a positive self-perception of health. Nervousness, autonomic symptoms and fear stood out among the anxious symptoms. Regarding depressive symptoms, most reported self-criticism, irritability, fatigue, pessimism and sleep disorders. Positive expectations regarding the future were prevalent in the sample. Conclusion: The COVID-19 pandemic has challenged the health of the academic community. The students experienced the second wave with psycho-emotional reactions, but also with various coping strategies, mainly related to affective support from family and friends and professional support. The results show the need to investigate daily life, its stressors and risk factors to provide adequate support to promote and maintain the health of these students by approaching protective factors.